II. DIFFERENCES IN ADRENAL MEDULLA NUCLEAR DNA CONTENT AMONG RATS OF DIFFERENT STRAINS FOLLOWING INTERMITTENT EXPOSURE TO COLD - Tongiani, Roberto (The Rockefeller University Press, 1969)
The amount of DNA per nucleus in the adrenal medulla cells of four different strains of rats (Wistar, Sprague-Dawley, Long-Evans, and Italico) is determined both under control conditions and after 300 hr of intermittent exposure to cold. The adrenal medulla nuclei of the four strains of rats contain the same amount of DNA; however, the loss of DNA observed after the same experimental treatment differs markedly in the different strains. The loss is small in Wistar and Sprague-Dawley rats (8–13%), larger in Long-Evans rats (20%) and still larger in Italico rats (45%). The DNA loss in Wistar rats increases if the animals are fed the same diet as the Italico rats, and the DNA loss in Italico rats is reduced if the animals are fed the same diet as the Wistar rats. The different behavior of the four strains is discussed in terms of turnover of DNA.